DNA BARCODING LIBRARY DATABASE OF AQUILARIA MEMBER AND GYRINOPS MEMBER - Wangiyana, I Gde Adi Suryawan (Jurnal Silva Samalas, 2020)
Aquilaria and Gyrinops are the primary agarwood producer on international trade. For authentication and standardization purposes, it is essential to carry DNA barcoding studies of these genera. DNA barcoding studies on plants need a database of several regions on the plant genome that could act as a barcoding marker. These DNA barcoding markers could be divided into Chloroplasts barcoding and Nuclear barcoding. Several markers have been used for DNA barcoding study of agarwood producer species, including trnL-trnF, matK, rbcL, rpoC1, ycf1 (Chloroplast barcoding), and ITS (Nuclear barcoding). This review breakdown the availability of those DNA barcoding markers on the online genebank database for Aquilaria and Gyrinops. Aquilaria genus has 12 species members, while Gyrinops genus has six species members. The sequence of region trnL-trnF is the only barcoding marker covering all 12 species members of Aquilaria and six species members of Gyrinops. Both ITS and matK have covered nine species among 12 total species members of Aquilaria. The rbcL, rpoC1, and ycf1, respectively, have covered eight, five, and four species members of Aquilaria. Most of the barcoding markers have covered three species members of Gyrinops except for ITS (5 species) and rpoC1 (1 species). However, Gyrinops members have no ycf1 sequence on genebank database. Based on sequence availability on the genebank database, it could be concluded that the trnL-trnF region is the most promising DNA barcoding marker for the Aquilaria and Gyrinops members especially for the phylogenetic analysis purpose.